Implementation of Dialectical Behavior Therapy with Suicidal and Self-Harming Adolescents in a Community Clinic. Issue 1 (2nd January 2020) - Berk, Michele S.; Starace, Nicole K.; Black, Vanessa P.; Avina, Claudia
Abstract : The object of this research was to examine the feasibility and effectiveness of Dialectical Behavior Therapy (DBT) with suicidal and self-harming adolescents treated in a community clinic. A group of 24 adolescents at high risk for suicide were enrolled in 6 months of comprehensive DBT, provided by therapists and trainees at a county-run outpatient mental health clinic serving disadvantaged, ethnic minority clients. Results showed significant pre/post-treatment decreases in suicide attempts, non-suicidal self-injury behaviors (NSSI), and suicidal ideation. Results also showed significant decreases in other suicide risk factors, including emotion dysregulation, depression, impulsivity, BPD symptoms, psychopathology, PTSD symptoms, and substance use, as well as increases in family expressiveness and reasons for living. Treatment retention and satisfaction rates were high. As many youth at risk for suicide will be treated in community settings, findings showing that receiving DBT in a community clinic resulted in significant improvements across a range of suicide risk factors are an important contribution to the adolescent suicide prevention literature.